PEREMPUAN DAN LALAMPA: PERKEMBANGAN KEHIDUPAN SOSIAL EKONOMI PENJUAL LALAMPA DI TOBOLI - Wahyudi, Imam (Manaqib: Jurnal Sejarah Peradaban Islam dan Humaniora, 2022)
The problems in this paper are (1) What are the reasons women in Toboli choose to become lalampa sellers? (2) How is the development of the lalampa culinary business in Toboli? (3) How is the socio-economic development of lalampa sellers in Toboli? This study uses a descriptive qualitative method with a historical approach. Data collection techniques used are literature studies and field studies consisting of observations, interviews, and documentation. This research was conducted in Toboli Village, North Parigi District, Parigi Moutong Regency. The results of this study found three conclusions, namely: First, there are five factors that cause women to become sellers of lalampa, which are driven by increasing economic needs, women's educational background, domestic roles inherent in women, the background of life raised in a merchant environment, and being motivated or having a desire to follow the previous successful lalampa sellers; Second, Toboli lalampa is a culinary commodity that has become an economic commodity for women in Toboli and has become the identity of Toboli itself; Third, the development of Toboli's lalampa culinary business has changed the roles, duties, and functions of women in the family. Now, the women selling lalampa in Toboli have become the economic support for their families and also they have contributed greatly to raising the socio-economic status of their families.